2018
DOI: 10.1111/acv.12435
|View full text |Cite
|
Sign up to set email alerts
|

Refuge as major habitat driver for wolf presence in human‐modified landscapes

Abstract: Despite severe population declines and an overall range contraction, some populations of large carnivores have managed to survive in human-modified landscapes. From a conservation perspective, it is important to identify the factors allowing for this coexistence, including the relevant habitat characteristics associated with the presence of large carnivores. We evaluated the role of several environmental factors describing habitat quality for wolves Canis lupus in the humanised Iberian Peninsula, which current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…One study found that topographic indices better explained Rhododendron richness at coarse scale (grain size >1°), while another study similarly found that bird species richness was better explained at coarse grain sizes (40 and 80 km resolution) owing to climate, topography and human land use operating on these scales (Yamaura, Amano, Kusumoto, Nagata, & Okabe, ; Yu et al, ). Likewise, a recent study found that topography acted as a refuge for wolves ( Canis lupus ) at several spatial scales (Grilo et al, ). As the choice of grain size depends on both the available species and environmental data and the modeling objectives, we argue that using a county‐level resolution in this study matches the study question since we expect to see the effects of topography at this landscape level.…”
Section: Discussionmentioning
confidence: 98%
“…One study found that topographic indices better explained Rhododendron richness at coarse scale (grain size >1°), while another study similarly found that bird species richness was better explained at coarse grain sizes (40 and 80 km resolution) owing to climate, topography and human land use operating on these scales (Yamaura, Amano, Kusumoto, Nagata, & Okabe, ; Yu et al, ). Likewise, a recent study found that topography acted as a refuge for wolves ( Canis lupus ) at several spatial scales (Grilo et al, ). As the choice of grain size depends on both the available species and environmental data and the modeling objectives, we argue that using a county‐level resolution in this study matches the study question since we expect to see the effects of topography at this landscape level.…”
Section: Discussionmentioning
confidence: 98%
“…The Iberian Peninsula contains extensive areas outside the present wolf range where human appropriation of primary production (Haberl et al 2007) is presently comparable to that of areas used by wolves. Habitat suitability analyses recently reported that substantial habitat exists outside the present wolf range, both at a fine spatial scale that would reflect suitability as breeding habitat, and at coarser spatial scales that would indicate presence and traversing suitability (Grilo et al 2018). In addition to overall habitat availability, an important fraction of wolves' former range in Iberia includes areas listed as candidates to the Natura 2000 network of protected areas (European Environment Agency 2018), especially south of the Douro River and in the central part of the Iberian Peninsula.…”
Section: Other Plausible Factors Limiting Range Recoverymentioning
confidence: 98%
“…For example, elevated forested areas tended to be occupied by both brown bears and grey wolves. Elevated forests (of 1 km 2 ) and complex topography areas may be selected by (Canis lupus) wolf pairs for refuge and breeding (Grilo et al 2019) far from other grey wolf pairs (source populations) (Ražen et al 2016). It can be inferred that brown bears could use the same forested areas for food by displacing grey wolf (pairs) from their kills.…”
Section: Potential Biotic Interactions Between Brown Bears and Wolvesmentioning
confidence: 99%